The Goal Setting of Internal Control in the System of Project Financing - Anna V. Bodiako; Svetlana V. Ponomareva; Tatyana M. Rogulenko; Marina Karp; Elena Kirova; Viktor Gorlov; Anna Burdina (International Journal of Economics and Financial Issues, 2016)
The article deals with the problems of internal corporate control over the formation of financial resources for particular economic projects of technological re-equipment of expanded reproduction factors (tools and objects of labor, labor organization and motivation). Two main objectives were stated in the article. The first one is to identify the dependency of the dynamics of the planned financial capacity of innovative projects, their actual coverage and results received upon the completion of project works that are the subjects and objects of internal corporate control. The second one objective is to rationalize the effectiveness of internal corporate control methods, depending on the choice of control rules, established by the legislative acts of the Russian Federation. The methods of economic analysis – comparison, grouping and balance method of data systematization were used. The lack of motivation of control subjects to revealing the risks of project financing was identified. The measures were offered to improve the efficiency of internal corporate control, providing innovative activity of business entities by optimizing the sources of projects financing and expansion of financial information in the notes to financial statements.